On the dynamics in parameter planes of the Lorenz-Stenflo system - Rech P.C.* (2015)
© 2015 The Royal Swedish Academy of Sciences.We report parameter planes displaying dynamical behaviors of the four-variable, four-parameter Lorenz-Stenflo system, which describes the time evolution of nonlinear low-frequency short-wavelength gravity wave disturbance in a rotating atmosphere. All the six parameter combinations two by two are considered. By using Lyapunov exponents spectra to characterize the dynamics of the Lorenz-Stenflo system, we show that hyperchaos is not present. Chaotic, quasiperiodic, periodic, and equilibrium point regions are delimited in the considered parameter planes.